(untitled) (Linguamática, 2013)
What formalism should be used in order to formalize natural language? That formalism must be able to describe all sequences of natural languages in a right way. Moreover, as long as possible, that formalism must be simple, with a reduced computational cost. This question has triggered a great controversy among the main branches of generative Linguistics: Transformational Grammar and Unification Grammars. The claim of this paper is that, despite discrepancies, these linguistic models formalize natural language by means of the same formal language. This is a well-defined formal language: the context-sensitive language of Noam Chomskyâ€™s hierarchy. So, from the point of view of this paper, nowadays, Linguistics can oâ†µer an unified computational model of natural language.